The Implementation of Shari’a in Aceh: Between the Ideal and Factual Achievements - Muhammad Amin Suma; Ridwan Nurdin; Irfan Khairul Umam (AHKAM : Jurnal Ilmu Syariah, 2020)
Aceh becomes the only region in Indonesia, where Islamic law is formally implemented. This paper aims at discussing the implementation of shari’a in Aceh, to compare between its ideal and factual achievements. Employing a qualitative socio-legal approach, data is obtained from interviews with the chairperson of Ulama’s Consultative Assembly (Majelis Permusyawaratan Ulama), head of Shari’a Office (Dinas Syariah), scholars, and community leaders. Apart from that, an observation was undertaken to record the process of whipping punishment. This study finds out that shari’a implementation in Aceh has been sufficiently supported by shari’a institutions (MPU and Shari’a Office), religious figures, community, and available punishment execution for the violators. However, some aspects need to be improved, especially those that are related to the role of other law enforcers such as police, prosecutors, and judges; and sustainable socialization.  AbstrakAceh menjadi satu-satunya provinsi di Indonesia yang menerapkan syariat Islam secara formal. Penelitian ini  mengkaji penerapan syariah di Aceh dengan membandingkan antara yang ideal sebagaimana diharapkan dan yang faktual. Dengan menggunakan pendekatan kualitatif dan sosio-legal, data diperoleh melalui wawancara dengan Majelis Permusyawaratan Ulama, Dinas Syariah, akademisi, dan tokoh masyarakat. Selain itu, observasi dilakukan untuk melihat pelaksanaan hukuman cambuk.  Hasil penelitian ini menunjukkan bahwa implementasi syariah di Aceh sudah didukung dengan institusi syariah (MPU dan Dinas Syariah), dan tokoh agama, masyarakat. Adanya eksekusi bagi pelanggar hukum menguatkan pelaksanaa syariah di daerah itu. Akan tetapi, ada pula aspek-aspek yang perlu ditingkatkan, yaitu peran penegak hukum seperti polisi, jaksa, hakim, dan juga keberlangsungan sosialisasi kepada masyarakat.